Teachers’ and Students’ Perceptions of Ai and Deep Learning Intergration in English Instruction at Junior High School - Ismi Islamia R Iswari (Trigin Institute, 2026)
This study aims to examine teachers’ and students’ perceptions of Artificial Intelligence (AI) and deep learning integration in English instruction at junior high schools. AI and deep learning are expected to serve as learning-support technologies by providing additional resources, adaptive feedback, and more guided practice, while teachers continue to guide learning strategies. The research employed a descriptive quantitative design using questionnaire data collected from English teachers and junior high school students. The questionnaire items measured participants’ understanding of AI and deep learning concepts, perceived usefulness of AI features (such as learning resources, feedback, grammar checking, and speaking practice), perceived ease and readiness to use AI tools, perceived challenges or limitations, and perceived expectations for teacher support and classroom integration. Data were analyzed using descriptive statistics, including frequency counts, percentages, and mean scores, with potential comparative analysis between teacher and student perceptions. The findings indicate that AI-assisted deep learning positively supports all four English language skills reading, writing, speaking, and listening through faster assistance in comprehension, grammar and writing corrections, engaging speaking practice with instant feedback, and listening support using transcripts and adjustable exercises. However, several negative impacts were also identified, including students’ overreliance on AI that may reduce independent learning, the possibility of AI outputs that do not align with context or students’ proficiency level, challenges related to device and internet/audio quality, and concerns about alignment with curriculum objectives if AI use is not properly guided. Overall, the study suggests that AI integration can enhance learning effectiveness and motivation, but requires appropriate teacher direction, careful tool selection, and alignment with curriculum competencies to maximize benefits and minimize limitations